Therapeutic Potential of Wheatgrass Juice: A Comprehensive Narrative Review - Deepak Bangera; Farha R. Sikalgar; Prajna P. Shetty; Rashmitha Alva; Yuvaraj Paul; Shrikanth Muralidharan (Journal of Pharmacy and Bioallied Sciences)
Wheatgrass juice (WGJ), extracted from the young grass of Triticum aestivum, is an emerging natural health remedy with diverse therapeutic properties. Its rich composition of chlorophyll, vitamins, minerals, amino acids, and antioxidants makes it a functional food with potential applications in managing chronic diseases and promoting overall health. WGJ has demonstrated efficacy in reducing oxidative stress, improving hemoglobin levels in anemia, detoxifying the body, and enhancing immunity. Additionally, it has shown promise as an adjunct in cancer treatment, cardiovascular health, and gastrointestinal disorders. Despite its broad usage, most of the evidence supporting WGJ’s benefits comes from limited studies, emphasizing the need for more rigorous scientific validation. This narrative review explores the nutritional profile, bioactive compounds, and therapeutic applications of WGJ while addressing its limitations and potential for integration into modern medicine.